LOCAL ORGANIZATIONAL CAPACITY IN NATURAL DISASTER MANAGEMENT IN PAGERWANGI VILLAGE, BANDUNG BARAT DISTRICT - Bekti, Herijanto (Jurnal Multidisiplin Sahombu, 2023)
The community is the main actor in disaster management in their area. Involvement as explained by The international strategy for disaster risk reduction (UNDP: 2006) which is one of the strategies by involving community participation in the implementation of disaster risk reduction. The involvement of the community in disaster management policies has been carried out by the government of West Bandung Regency through a disaster resilient village program implemented by the Regional Disaster Management Agency (BPBD). The program is intended to establish and foster local communities for disaster management. This means that the community is facilitated to be involved in disaster management through local organizations formed by the government. Then the local Institution in Pagerwangi Village, Lembang Subdistrict, West Bandung Regency in disaster management is still in the process of developing its resources. The knowledge of organization members about disaster management provides a barrier to the process of strengthening the capacity of local organizations, especially in natural disaster management. So far what has been done is still waiting for encouragement from the local government of West Bandung Regency and from the internal organization itself.